Self-Control, Risky Behavior, and Dating Application-Facilitated Victimization - Centelles, Vanessa (Victims & offenders, 2022)
The increased connectivity on mobile platforms – including dating applications – is associated with increased risks of victimization both online and in-person. The current study explores the role of dating applications in shaping the risk(s) of victimization. Using a sample of college students (N = 324), we examine the relationship between low self-control and victimization (online and in-person), and the mediating effect of risky behavior, finding that low self-control is associated with in-person victimization, although partially mediated by risky behavior. Low self-control was not a significant predictor for cybervictimization. We also discern gendered effects in both engagement of risky behaviors and experiences of victimization.